The miseducation of the West : how schools and the media distort our understanding of the Islamic world - Kincheloe, Joe L.; Steinberg, Shirley R., 1952- (Reverberations (Praeger Publishers), 2004)
The Miseducation of the West examines the ways in which educational institutions such as media and schools have shaped Western views of Islam. The nature of these messages tells readers as much, if not more, about Western self-images as they do about Islam and Islamic peoples. Quickly emerging is a Western perspective on the other. Westerners found easy justification for the colonial conquest of many Islamic lands. In the 18th, 19th, and early 20th centuries England, France, and to a lesser extent Russia colonized much of the Mulsim world with the United States entering the picture after World.